The impact of bedding materials and disinfectants on udder health and mastitis control in dairy cows - Shahedani, MS; Ahmadi, F; Tosun, Hİ (Journal of the Hellenic Veterinary Medical Society, 2024)
This study investigates the influence of disinfectants applied in bedding areas on mastitis prevalence in dairy farming, emphasizing the critical relationship between bedding materials, disinfectants, and udder health indicators. The importance of this research lies in its potential to enhance evidence-based strategies for mitigating mastitis risk, a significant concern in the dairy farming sector. The existing research gap pertains to a comprehensive understanding of how specific bedding materials and disinfectants impact udder health indicators and mastitis prevalence. Our research questions focus on discerning the associations between these variables and their collective impact on somatic cell count and mastitis prevalence. Employing multivariate regression and correlation analyses, we elucidate the intricate relationships among influential factors affecting udder health in dairy farming. The key message of our study underscores the pivotal roles of bedding materials and disinfectants in influencing udder health outcomes. Our findings reveal statistically significant associations between herd size, bedding materials, disinfectants, and udder health indicators. Larger herd sizes are linked to lower mastitis prevalence, and specific bedding materials, such as bagasse, show promising results in reducing mastitis risk. The study contributes practical insights for dairy farmers to optimize udder health by making informed choices in bedding materials and disinfectants. The findings emphasize the importance of considering specific factors in bedding materials and disinfectants for sustainable improvements in dairy farm outcomes.